Pengembangan Instrumen Tes Keterampilan Proses Sains pada Materi Biologi Sistem Regulasi Tumbuhan Kelas XI SMA - Awaliyah, Walidatul; Fuadiyah, Sa'diatul (CV. PUSDIKRA MITRA JAYA, 2025)
Learning becomes more impactful when students can identify and understand core scientific ideas, and one effective way to support this is by assessing their KPS during learning. To achieve this, educators can use assessment tools that are aligned with specific KPS indicators. In addition, there is currently no specific assessment tool that targets KPS in the context of the topic of plant regulatory systems. This study aims to produce a product in the form of a valid science process skills (KPS) instrument in biology learning on plant regulatory system material in class XI SMA. This type of research is research and development that adopts Plomp's development model which consists of three main stages, where this research is limited to two stages, namely preliminary research and prototyping phase. This research used Tessemer's formative approach which includes the stages of self evaluation and expert review. Data were analyzed qualitatively and quantitatively. Data collection instruments used interview sheets and expert validity questionnaires (expert review). Produk yang dikembangkan divalidasi dalam lima aspek penilaian, yaitu aspek materi, aspek konstruksi, aspek bahasa,aspek kegrafikaan, dan aspek Keterampilan Proses Sains (KPS) oleh 2 validator dosen biologi. Berdasarkan hasil penelitian diperoleh nilai validitas instrumen yaitu validasi ahli aspek materi 90%, aspek konstruksi 95%, aspek bahasa 91,6%, aspek kegrafikaan 87,5%, dan validasi aspek KPS 75%. Kesimpulan: instrumen tes keterampilan proses sains pada materi sistem regulasi tumbuhan dinyatakan valid.